2020
DOI: 10.1038/s41467-020-16121-y
|View full text |Cite
|
Sign up to set email alerts
|

A microsporidian impairs Plasmodium falciparum transmission in Anopheles arabiensis mosquitoes

Abstract: A possible malaria control approach involves the dissemination in mosquitoes of inherited symbiotic microbes to block Plasmodium transmission. However, in the Anopheles gambiae complex, the primary African vectors of malaria, there are limited reports of inherited symbionts that impair transmission. We show that a vertically transmitted microsporidian symbiont (Microsporidia MB) in the An. gambiae complex can impair Plasmodium transmission. Microsporidia MB is present at moderate prevalence in geographically d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(162 citation statements)
references
References 58 publications
2
131
2
1
Order By: Relevance
“…It was shown that the number of oocysts in microsporidian-infected mosquitoes is strongly reduced compared to uninfected ones (58% vs. 81%) [63]. Similarly, Microsporidia MB, which is another example of microsporidia with non-deleterious effects, is found in the midgut and ovaries of Anopheles arabiensis and alters the development of Plasmodium falciparum by stimulating the expression of genes encoding digestive enzymes such as serine proteases, as well as the immune response (cecropins and gambicins) [64]. Strains of W. anomalus unable to produce killer toxins reduce the intensity of P. berghei infection in Anopheles mosquitoes by 38% probably through the activation of the mosquito immune system [57].…”
Section: Indirect Impact Through the Modulation Of The Immune Systemmentioning
confidence: 99%
“…It was shown that the number of oocysts in microsporidian-infected mosquitoes is strongly reduced compared to uninfected ones (58% vs. 81%) [63]. Similarly, Microsporidia MB, which is another example of microsporidia with non-deleterious effects, is found in the midgut and ovaries of Anopheles arabiensis and alters the development of Plasmodium falciparum by stimulating the expression of genes encoding digestive enzymes such as serine proteases, as well as the immune response (cecropins and gambicins) [64]. Strains of W. anomalus unable to produce killer toxins reduce the intensity of P. berghei infection in Anopheles mosquitoes by 38% probably through the activation of the mosquito immune system [57].…”
Section: Indirect Impact Through the Modulation Of The Immune Systemmentioning
confidence: 99%
“…transmission. As a microbe that is nonvirulent and vertically transmitted, Microsporidia MB could be investigated as a strategy to limit malaria transmission (Herren et al, 2020).…”
Section: R4d Into Insect Symbiontsmentioning
confidence: 99%
“…More recently, a symbiont microsporidian (Microsporidia MB) that colonizes An. arabiensis from Kenya, was shown capable of blocking P. falciparum development and transmission, providing a new prospect for malaria control [201]. Host-baited traps, odour-baited traps, resting traps, and sugar-baited traps have been proposed as possible ways of delivering these agents to mosquitoes [202].…”
Section: Naturally Occurring Symbiotic Microorganisms With Anti-pathomentioning
confidence: 99%